Milli mücadele dönemi bütçeleri ve mali uygulamalar - Tekin, Ahmet (Afyon Kocatepe Üniversitesi, 2000)
Milli Mücadele bütçeleri savaş dönemi koşullarını taşıyan birer Savunma bütçesi niteliğine sahiptir. Bütçeler savaş nedeniyle çoğu kez süresinde çıkarılamamış, harcamalar alınan avanslarla gerçekleştirilmiştir. Bütçeler Ulusun kendi kaynaklarından finanse edilmiş, ancak sınırlı sayıda da olsa bazı devletlerin de Kurtuluş Savaşının kazanılmasında yardımı olmuştur.

The budgets during Turkish Independence War had the characteristics of defense budgets affected by the conditions of the war. Since these annual budgets could not be prepared and approved by the Parliament on time, necessary public expenditures were financed by advances. These annual budgets were mostly financed by the nation’s own resources, however, there were some foreign aids through from a limited number of countries.There were also some foreign that helped Turkish Nation to win independent war.
Keywords: Milli Mücadele Dönemi; Mali Uygulamalar